SAT0148 Cardiovascular Risk Estimation in Rheumatoid Arthritis: What is Missing in Traditional Risk Estimators?. (10th June 2014) - Ozen, G.; Sunbul, M.; Atagunduz, P.; Direskeneli, H.; Tigen, K.; Inanc, N.
Abstract : Background: Cardiovascular (CV) disease is one of the major causes of mortality in RA. Although the CV risk in RA is well-recognized, detection of high risk patients and prevention of CV disease are still major challenges. Objectives: To determine which CV risk estimation index is better in RA patients and to determine the factors that may improve CV risk estimation in RA. Methods: One-hundred and six consecutive RA patients without history of CV disease or diabetes mellitus were assessed. Systematic Coronary Risk Evaluation (SCORE) and 2013 American College of Cardiology/American Heart Association (ACC/AHA) 10-year atherosclerotic CV disease risk (ASCVD) indices and their modified versions (mSCORE and mASCVD risk) according to EULAR recommendations were calculated. All patients were evaluated with carotid ultrasonography (US). Carotid intima-media thickness (cIMT) >0.90 mm and/or carotid plaques were used as the gold standard test for subclinical atherosclerosis and high CV risk (US+). Results: The study cohort consisted of 106 RA patients (F/M=93/13, mean age 51.7±11.3) with a mean disease duration of 9.9±6.2 years. RF and anti-CCP positivity were 78.3% and 61.3%, respectively. The EULAR multiplier factor was used in 41 (38.6%) patients. The mean mSCORE was 1.70±2.95% and mASCVD risk was 4.4.1±5.83%. The mSCORE defined 6 (5.7%) patients and mASCVD defined 28 (26.4%) patients as having high/very high CV risk (mSCORE≥5%, mASCVD≥7.5%). Concerning US results, 28 (26.4%) patients had either cIMT>0.90 mm or carotid plaques. The mASCVD risk better identified US+ patients, that of the US+ patients 16 (57.1%) were in mASCVD high/very high risk group whereas only 4 (14.3%) of the US+ patients were in high/very high risk group according to mSCORE ( P <0.0001). However mASCVD risk still has failed to identify 42.9% of US+ patients. When traditional risk factors and disease characteristics of US+ and US – patients were compared, it was found that US+ patients were older at diagnosis, had higher triglyceride levels and erythrocyte sedimentation rates. Furthermore current methotrexate use was lower in US+ patients along with similar rates of biologic treatment and other traditional risk factors (Table 1 ). Conclusions: EULAR recommendation for CV risk assessment, SCORE, seems inadequate even after modification according to RA characteristics. On the other hand ACC/AHA 10-year ASCVD risk index is better in estimating CV risk in RA patients. However, still additional modificiations, like age at disease onset, methotrexate usage, ESR are required to fully identify high-risk RA patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3063